The percentage of HIV treatment and prevention services in Kenya provided by faith-based health providers. Issue 5 (4th July 2017) - Blevins, John; Kiser, Mimi; Lemon, Emily; Kone, Ahoua
ABSTRACT: Although the percentage of health services provided by the faith-based sector in sub-Saharan Africa is often cited along a range from 30% to 70%, depending on the country, such citations tend to be anecdotal and without reference to actual analysis of health service data. This article reports on a secondary analysis of health service data in Kenya to determine the percentage of HIV services provided by faith-based health providers. It then discusses the contributions of faith-based providers in light of these data, identifying opportunities and challenges involved in efforts to ensure that the resources of the faith-based sector are maximised.